A Novel Mobility Concept for Terrestrial Wheel-Legged Lunar Rover - Mubarak Yakubu; Yahya Zweiri; Laith Abuassi; Rana Azzam; Ahmad Abubakar; Amna Busoud; Lakmal Seneviratne (IEEE Access)
The mobility system of lunar rovers is crucial for the success of space exploration missions. Existing mobility systems face significant challenges in navigating rough and complex terrains. In this paper, we present a novel mobility system for a wheel-legged lunar rover that utilizes a single motor along with an assembly of bevel gears, electromagnetic clutches, and worm gears to control the articulation of four legs, achieving a total of 15 degrees of freedom (DoF). This mobility concept offers the advantage of a self-locking function, which secures the leg positions even in the event of component failure - an improvement over systems with individual motors for each leg. A prototype space rover, the Khalifa University Space Rover (KUSR), was built based on the proposed system and tested in both simulations and real-world experiments. A series of tests were conducted to compare the performance of KUSR with that of the Rashid rover and the Japan Aerospace Exploration Agency’s MMX rover. The results demonstrate that KUSR can effectively overcome obstacles greater than 20 cm in height and steep slopes greater than 40°. Performance was evaluated based on the successful completion of each task. KUSR achieved an average success rate of 82.08%, compared to 80.42% for the MMX rover and 52.08% for the Rashid rover. When failure was introduced in the motors, KUSR achieved a success rate of 52.6% due to the self-locking capability of the system, compared to 12.6% for the MMX rover. A supplementary video is available at https://youtu.be/-TbM14IcnRE.